Long-Term Investigation of Emissions and Economic Growth in Developed and Developing Countries: A Bibliometric Analysis - Indriawati, Ratna Malisa; Gravitiani, Evi; Soesilo, Albertus Maqnus; Cahyadin, Malik (International Journal of Energy Economics and Policy, 2023)
This study seeks to present a better knowledge mapping of emissions and economic growth by referring to literature reviews in developed and developing countries from 2000 to 2022. This study provides overviews of a bibliometric approach, namely: time analysis, journal, co-authorship, citation, country, and institution. The literature survey uses the causality’s direction between (i) emissions and economic growth, and (ii) emissions in developed and developing countries. The degree of research contribution in developed and developing countries has an upward trend in recent years. Journal analysis reveals that Environmental Science and Pollution Research is the journal with the most contributions to analyses in developed and developing countries. Furthermore, the citation analysis shows that "Growth in Emission Transfers via International Trade from 1990 to 2008" has the highest author citations. This study suggests that research collaboration between developed and developing countries can be promoted in producing sustainable green economic growth.